INTEGRATED MARKETING COMMUNICATION TEH SEPEDA BALAP AGEN SOLO MELALUI BRAND AMBASSADOR WHAWIN LAWRA - Hayu Pintari; Andri Astuti Itasari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
Teh Sepeda Balap is one of the tea companies that is quite popular, especially in Central Java. Teh Sepeda Balap has distributor agents spread throughout Indonesia, one of which is the city of Solo. In marketing its products, Teh Sepeda Balap Agen Solo applies a new marketing communication called Integrated Marketing Communication. In Integrated Marketing Communication there are six elements of marketing communication, namely advertising, direct marketing, sales promotion, public relations, word of mouth, event and experience. The most prominent marketing communication from Teh Sepeda Balap is event and experience and focuses on business partners. Teh Sepeda Balap has a vision of becoming a popular tea, for that Teh Sepeda Balap tries as much as possible to establish closeness with the people. In its promotional efforts, Teh Sepeda Balap (Racing Bike Tea) partners with brand ambassadors whose personalities and vision align with Teh Sepeda Balap’s. For the Greater Solo area, Teh Sepeda Balap’s Solo Agent appointed Whawin Lawra as its brand ambassador. Whawin Lawra is a singer with a friendly, cheerful, humorous personality and a close relationship with the community. Therefore, Teh Sepeda Balap appointed Whawin Lawra as its brand ambassador as a form of marketing communication. Keywords; Integrated Marketing Communication, brand ambassador